Primary teachers' representational practices: from competency to fluency. Issue 4 (1st October 2016) - Nichols, Kim; Stevenson, Michael; Hedberg, John; Gillies, Robyn Margaret
Abstract : Eighteen primary teachers across three conditions (Representational Fluency, Representational Agency, Comparison) received two days of training around an inquiry unit on plate tectonics replete with representations. The Representational Agency group also received training around the semiotic and material affordances of representations while the Representational Fluency group received this and additional training in making conceptual connections between representations. A pre-test and post-test around making conceptual connections between representations was provided. Interviews were conducted at the end of the unit. Tests were analysed using the SOLO taxonomy. Interview transcripts were analysed for levels of use of representational practices. Teachers in all conditions showed improved abilities to make conceptual connections between representations. The Representational Fluency group was better at making conceptual connections between representations and showed the highest uptake of representational practices. However, development of representational fluency (making conceptual connections between representations) is not always correlated with a higher uptake of representational practices.